ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE DALAM PENGELOLAAN ZAKAT PADA LAZNAS YATIM MANDIRI JEMBER - Mahyuddina Almas; Bahrina Almas (Negotium: Jurnal Ilmu Administrasi Bisnis, 2023)
ABSTRACTGood Corporate Governance at the Zakat Management Institution (LPZ) aims to measure and assess the performance management of an institution in terms of managing Zakat, Infaq, and Shadaqah (ZIS) funds in a professional manner in increasing the trust of stakeholders (muzakki). Yatim Mandiri Jember as one of the National Amil Zakat Institutions needs to apply the principles of good corporate governance in zakat fund management activities. The purpose of this study was to find out about the application of the principles of good corporate governance in the collection and distribution of zakat funds at the Yatim Mandiri National Amil Zakat Institute Jember. This study uses a qualitative approach with the type of field research (field research). The results of the study indicate that LAZNAS Yatim Mandiri Jember has implemented the principles of good corporate governance in the activities of collecting and distributing zakat funds. LAZNAS Yatim Mandiri Jember routinely provides open financial reports to muzakki, division of organizational structure and assignment of tasks according to the field of expertise, zakat management is in accordance with applicable laws and regulations and the institution is responsible for muzakki and mustahik needs.Keywords: Good Corporate Governance, Management, ZakatABSTRAKGood Corporate Governance pada Lembaga Pengelola Zakat (LPZ) bertujuan untuk mengukur dan menilai tata kelola kinerja pada suatu lembaga dalam hal pengelolaan dana Zakat, Infak, dan Shadaqah (ZIS), secarabahofesional dalam meningkatkan kepercayaan dari para stakeholder (muzakki), sehingga manfaat yang diberikan kepada para mustahik (penerima zakat) akan semakin besar dan maksimal. Yatim Mandiri Jember sebagai salah satu Lembaga Amil Zakat Nasional perlu menerapkan prinsip good corporate governance dalam kegiatan pengelolaan dana zakat. Tujuan penelitian ini adalah mengetahui tentang penerapan prinsip good corporate governance dalam penghimpunan dan pendistribusian dana zakat di Lembaga Amil Zakat Nasional Yatim Mandiri Jember. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian lapang (field research). Hasil penelitian menunjukkagn bahwa LAZNAS Yatim Mandiri Jember telah menerapkan prinsip good corporate governance dalam kegiatan penghimpunan dan pendistribusian dana zakat. LAZNAS Yatim Mandiri Jember secara rutin memberikan laporan keuangan secara terbuka kepada para muzakki, pembagian struktur organisasi dan pemberian tugas sesuai dengan bidang keahian, pengelolaan zakat telah sesuai dengan peraturan perundang-undangan yang berlaku dan lembaga bertanggungjawab terhadap para muzakki dan kebutuhan mustahik.Kata Kunci: Good Corporate Governance, Pengelolaan, Zakat